2011
DOI: 10.1074/jbc.m110.126706
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Analysis of Cathepsin K/Chondroitin 4-Sulfate Interactions

Abstract: In the presence of oligomeric chondroitin 4-sulfate (C4-S), cathepsin K (catK) forms a specific complex that was shown to be the source of the major collagenolytic activity in bone osteoclasts. C4-S forms multiple contacts with amino acid residues on the backside of the catK molecule that help to facilitate complex formation. As cathepsin L does not exhibit a significant collagenase activity in the presence or in the absence of C4-S, we substituted the C4-S interacting residues in catK with those of cathepsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 25 publications
1
50
1
Order By: Relevance
“…The structures have been refined to 2.62 Å (DS) and 2.02 Å (C4-S) with data collection and refinement statistics summarized in Table S1. The overall structure of CatK in both complexes is highly similar to previously published structures (18,20). Superposing these structures on CatK-E64 C4-S structure [Protein Data Bank (PDB) ID code 3C9E] shows a CatK rmsd of (0.373) for the DS and (0.311) for the C4-S complex.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The structures have been refined to 2.62 Å (DS) and 2.02 Å (C4-S) with data collection and refinement statistics summarized in Table S1. The overall structure of CatK in both complexes is highly similar to previously published structures (18,20). Superposing these structures on CatK-E64 C4-S structure [Protein Data Bank (PDB) ID code 3C9E] shows a CatK rmsd of (0.373) for the DS and (0.311) for the C4-S complex.…”
Section: Resultssupporting
confidence: 56%
“…The C4-S and DS GAGs in our structures both reveal a linear orientation of the sugar chain in contrast with the previously published cosine-curved shape of C4-S (18,20). We speculate that the conformation of the GAG chain is determined by adopting an optimal fit into the binding site it docks into, as has been previously proposed (22).…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…Numerous in vitro studies have demonstrated that activated CatK inefficiently degrades collagen in solution, requiring several hours for ϳ2 M of activated CatK at the optimal acidic pH to digest just a few micromolar concentration of collagen type I (2,32,33). This apparently weak collagenase activity of CatK in vitro is not consistent with the efficient removal of bulk collagen during osteoclastic bone resorption, suggesting that other factors may enhance the collagenase activity of CatK.…”
Section: Cathepsin K (Catk)mentioning
confidence: 76%
“…Unlike the MMPs, cathepsins are single domain proteases which do not rely on additional modules to bind to their extracellular matrix substrates (Turk et al, 2001). However, the collagenolytic activity of cathepsin K is dependent on the presence of chondroitin 4-sulfate CS (Li et al, 2000) a major component of the aggrecan molecule which forms well-defined complexes with the enzyme (Cherney et al, 2011). While it was originally assumed that cathepsin K is unique to the osteoclast (and this cell does indeed contain huge amounts of the protease), many other cell types are now known to produce the enzyme (Anway et al, 2004;Sukhova et al, 1998).…”
Section: Cathepsinsmentioning
confidence: 99%